Robotics facial expression of anger in collaborative human–robot interaction. (4th January 2019) - Reyes, Mauricio E; Meza, Ivan V; Pineda, Luis A
The facial expression of angry emotion can be useful to direct the interaction between agents, especially in unclear and cluttered environments. During the presence of an angry face, a process of analysis and diagnosis is activated in the subject that notices it, which could impact its behavior toward the one who expresses the emotion. In order to study such an effect in human–robot interaction, an expressive robotics face was designed and constructed. The influence of this face on human action and attention was analyzed in two collaborative tasks. Results of a digital survey, experimental interaction, and a questionnaire indicated that anger is the best recognized universal facial expression, has a regulatory effect in human action, and induces human attention when an unclear condition arises during the task. An additional finding was that the prolonged presence of an angry face reduces its impact compared to positive expressions.